ANALISIS PENDAPATAN PETANI DAN PEMASARAN PADI ORGANIK DI DESA LIMAN SARI KECAMATAN BUAY MADANG TIMUR KABUPATEN OKU TIMUR - Muridin (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2016)
The purpose of this research were to : (1) To analyze the income and feasibility of organic rice farming in Liman Sari Village, East Buay Madang District, OKU Timur Regency, (2) To analyze the organic rice marketing margin in Liman Sari Village, Buay Madang Timur Sub-district, OKU Timur Regency , (3) To analyze the prospect of farming development and marketing of organic rice in Liman Sari Village, Buay Madang Timur Sub-district, OKU Timur Regency. This research was conducted in Liman Sari Village, Buay Madang Timur Sub-district, OKU Timur District of South Sumatera Province with farmer respondents who work on organic rice cultivation in the village. The selection of research sites is done purposively with the consideration that the area is one of the villages that has many farmers working on organic rice cultivation. The research data was collected for 3 (three) months from April to June 2014. The research found that farmers receiving from organic rice farm in Liman Sari Village at the time of research with the average of 0.33 hectare is Rp .7,936,073.00, and total cost of Rp.4.682.209, -, the average income of Rp.3.253.863, - is obtained. The average farming efficiency (R / C Ratio) of 1.70 indicates that organic rice farming in Liman Sari Village is profitable and feasible to develop. The average organic rice marketing margin obtained by Gapoktan Suko Rahayu Suko Rahayu is Rp.5.890 , - per kilogram, while the capital or marketing cost incurred is Rp.4.680, - per kilogram so as to obtain profit of Rp.1.210, - per kilogram and Prospect of development of organic rice farming in Liman Sari Village, Buay Madang Timur District East OKU Regency is In a weak but very likely position. The strategy recommendation is to change strategy, meaning that farmers and Gapoktan Suko Rahayu are advised to change the previous strategy. Therefore, the old strategy is feared difficult to be able to capture the opportunities that exist while improving the performance of the organization. One way is to take advantage of existing opportunities, seek capital lenders, improve labor skills, promote organic rice in electronic and printed media, and seek breakthroughs for organic rice to be widely accepted by the market.